International Investment Protection Made in Germany? On the Domestic and Foreign Policy Dynamics behind the First BITs - Ingo Venzke; Philipp Günther (European Journal of International Law, 2022)
The investment protection treaty concluded between Germany and Pakistan in 1959 is generally regarded as a milestone in the development of international investment law. It has entered the collective memory as the first bilateral investment treaty (BIT). In this article, we analyse archival sources to investigate why Germany and Pakistan concluded this agreement at that specific time and what makes this treaty the first of its kind. Through historical analysis, we trace the domestic and related foreign policies that led to the BIT and discuss the negotiation process. Our analysis shows that the BIT was so closely linked with the German federal investment guarantee scheme (Bundesgarantien) that it is best understood as an extension of that policy. This also helps us to specify the underlying rationale for the treaties. We further highlight the influence of the financial industry – especially of Hermann Josef Abs – on the genesis of the BIT, which was less decisive than is often suggested. We identify features of the 1959 BIT that do characterize it as a new international legal instrument, but nuance claims about its degree of innovation as well as underlying motivations, and counter considerable retrospective myth making.
Keywords: 330